PROCESS SKILL ERROR: THE MAJORITY STUDENT’S ERROR IN PROBLEM SOLVING OF INTEGRAL CALCULUS - Isnaeni Umi Machromah (Universitas Negeri Makassar, 2017)
There is high unpassed value of students in Mathematics Departmen UMS at Integral Calculus lecture. It is predicted that there are so many students have difficulties in Integral Calculus. Data from mid exam at academic year 2016/2017 showed that there are 80,87% from 115 students got score under 63. It is indicated that there are so many students’s error in solving integral calculus problems. Integral Calculus is one of basic lecture which is prerequisite of other complex lecture. Knowing the error’s position and the factor that caused student’s error would help lecturer pay attention in integral calculus learning. Thus, the aim of this research is identifiying error’s position that are done by students and analyzing causative factor in solving Integral Kalkulus problems. Kind of this research is qualitative description. Technique of collecting data is test and interview. This research uses technique-triangulation for validating data, it is by documentation and interview. Meanwhile, the steps for analyzing data are data reduction, data presentation, and conclusion. The result of this research showed that there is 41,40% error with type process skill error in solving Integral Calculus problems. Besides, types of student’s error in solving Integral Calculus problems are transformation error, comprehension error, and reading error. There is no encoding error that found in this research. Causative factors of that student’s error are (1) students did not careful in reading the problems, writing mathematics siymbol include symbol of integral, and calculating, (2) low of prerequisite material mastery and concept of basic mathematics, (3) low of undestanding of material and concept of integral, (4) students could not identify the characteristics or types of probles to determine the appropriate technique of integration, and (5) the use of formula which is not appropriate and not suitable with problem’s solution